The new evolutionary economics - Dopfer, Kurt; Potts, Jason 1972- (The international library of critical writings in economics, 2014)
This three volume set gathers together selected key articles in evolutionary economics, ordering these into the domains of micro analysis (concerned with agents), meso analysis (concerned with rule populations and trajectories) and macro analysis (concerned with the structure and development of the whole economy). This authoritative collection, with an original introduction by the editors, will be of interest to scholars and researchers seeking to understand how evolutionary economics fits together and to advance such an integrated approach.